Health professionals' views about who would benefit from using a closed‐loop system: a qualitative study. Issue 6 (14th February 2020) - Lawton, J.; Kimbell, B.; Rankin, D.; Ashcroft, N. L.; Varghese, L.; Allen, J. M.; Boughton, C. K.; Campbell, F.; Randell, T.; Besser, R. E. J.; Trevelyan, N.; Hovorka, R.; et al.
Abstract: Aim: To explore health professionals' views about who would benefit from using a closed‐loop system and who should be prioritized for access to the technology in routine clinical care. Methods: Health professionals (n = 22) delivering the Closed Loop from Onset in type 1 Diabetes (CLOuD) trial were interviewed after they had ≥ 6 months' experience supporting participants using a closed‐loop system. Data were analysed thematically. Results: Interviewees described holding strong assumptions about the types of people who would use the technology effectively prior to the trial. Interviewees described changing their views as a result of observing individuals engaging with the closed‐loop system in ways they had not anticipated. This included educated, technologically competent individuals who over‐interacted with the system in ways which could compromise glycaemic control. Other individuals, who health professionals assumed would struggle to understand and use the technology, were reported to have benefitted from it because they stood back and allowed the system to operate without interference. Interviewees concluded that individual, family and psychological attributes cannot be used as pre‐selection criteria and, ideally, all individuals should be given the chance to try the technology. However, it was recognized that clinical guidelines will be needed to inform difficult decisions about treatment allocation (and withdrawal), with young children and infants being considered priority groups. Conclusions: To ensure fair and equitable access to closed‐loop systems, prejudicial assumptions held by health professionals may need to be addressed. To support their decision‐making, clinical guidelines need to be made available in a timely manner. What's new?: Previous studies have overwhelmingly focused on users' perspectives and experiences of closed‐loop systems. This study offers an early and important insight into health professionals' views about who would benefit from using a closed‐loop system, and who should be prioritized for access to the technology in routine clinical care. Health professionals may hold prejudicial and erroneous views about the types of individual that would most benefit from using a closed‐loop system. Health professionals would benefit both from training to overcome these prejudicial assumptions and clinical guidelines to support decision‐making about allocating and withdrawing closed‐loop systems in routine clinical care.